2017
DOI: 10.1126/science.aak9611
|View full text |Cite
|
Sign up to set email alerts
|

Control and local measurement of the spin chemical potential in a magnetic insulator

Abstract: The spin chemical potential characterizes the tendency of spins to diffuse. Probing this quantity could provide insight into materials such as magnetic insulators and spin liquids and aid optimization of spintronic devices. Here we introduce single-spin magnetometry as a generic platform for nonperturbative, nanoscale characterization of spin chemical potentials. We experimentally realize this platform using diamond nitrogen-vacancy centers and use it to investigate magnons in a magnetic insulator, finding tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
304
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(313 citation statements)
references
References 55 publications
9
304
0
Order By: Relevance
“…For this purpose, it is of fundamental interest to develop a better understanding of magnon transport in magnetic insulators [14][15][16][17][18][19][20][21][22][23][24][25]. Analogous to the Aharonov-Bohm [26][27][28] (AB) effect of charged particles in magnetic fields, a magnetic dipole moving in electric fields acquires a geometric phase called the Aharonov-Casher [29,30] (AC) phase.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, it is of fundamental interest to develop a better understanding of magnon transport in magnetic insulators [14][15][16][17][18][19][20][21][22][23][24][25]. Analogous to the Aharonov-Bohm [26][27][28] (AB) effect of charged particles in magnetic fields, a magnetic dipole moving in electric fields acquires a geometric phase called the Aharonov-Casher [29,30] (AC) phase.…”
Section: Introductionmentioning
confidence: 99%
“…The applied temperature gradient ∂ x T induces a magnonic spin current for each magnon (σ =↑, ↓), j xσ = −L 12σ ∂ x T /T , which leads to an accumulation of each magnon at the boundaries and thereby builds up a non-uniform magnetization since two magnon modes are decoupled and do not interfere with each other in the AF. This generates an intrinsic magnetization gradient [71][72][73][78][79][80] …”
Section: B Thermomagnetic Relationsmentioning
confidence: 99%
“…II, the offdiagonal elements 76,77 similarly arise from the magnon counter-current by the thermally-induced magnetization gradient [71][72][73][78][79][80] …”
Section: Hall Conductances Of Magnonsmentioning
confidence: 99%
“…13,14 In particular, a growing body of research has focused on the interplay between the optically addressable nitrogen-vacancy (NV) center in diamond and spin wave (SW) excitations in extended ferromagnetic materials. [15][16][17][18][19] These systems have been proposed, for instance, as a platform to enable long distance coupling between NV centers, 15 by taking advantage of the SW's long damping length and the large interactions achievable through the ferromagnet's (FM) sizeable magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of recent works [16][17][18][19][20] revealed that the coherences of NV centers placed in proximity of a FM are strongly quenched by the magnetic field noise generated by driven ferromagnetic resonances. These results are of great interest for the implementation of broadband magnetic field sensing and for the study of the spin properties of ferromagnetic systems, but also suggest that incoherent mechanisms dominate the SW-NV center coupling.…”
Section: Introductionmentioning
confidence: 99%